Generic histories of German cinema : genre and its deviations - Fisher, Jaimey (Screen cultures., 2013)
"Generic Histories offers a fresh approach, tracing a series of key genres -- including horror, science fiction, the thriller, Heimat films, and war films -- over the course of German cinema history. It also addresses detective films, comedies, policiers, and romances that deliberately localize global genres within Germany - a form of transnationalism frequently neglected. This focus on genre and history encourages rethinking of the traditional opposition (and hierarchy) between art and popular cinema that has informed German film studies. In these ways, the volume foregrounds genre theory's potential for rethinking film history as well as cultural history more broadly."--Publisher's description.